HAMBATAN PENERJEMAHAN TEKS BAHASA ARAB KE DALAM BAHASA INDONESIA: PENGALAMAN MAHASISWA SASTRA ARAB UNIVERSITAS NEGERI MALANG - Irhamni Irhamni (Fakultas Sastra Universitas Negeri Malang, 2011)
This paper is intended to describe the result of a research focusing on the students’ translation problems in translating Arabic texts into Indonesian. The problems result from the students’ understanding and retelling (re-expressing) the results of the understanding during the translation process. In this study, the researcher is applying descriptive-qualitative method. The result shows that the students’ problems in translating have close relation with (1) the students’ understanding of linguistics structure and non-linguistics structure, and (2) the students’ problems in retelling (re-expressing) the results of their reading regarding linguistics and non linguistics problem.